Hubungan Pengetahuan Terhadap Deteksi Dini Kanker Leher Rahim Di Kawasan Pesisir Dan Kepulauan Ambalau - Zubaeda Zubaeda; Arindiah Puspowindari; Sumirda Rahareng (Jurnal Medika Nusantara, 2023)
Ca Cervix at the fourth rank from all of oncology in women in the word after ca mamae, colorectum and lungs. Early detection use IVA method. Data in 2021, from 390 women in fertile age who have early detection amounted 60 women (15%). This research determine to relationship knowledge with ca cervic early detection with IVA method in coastal and islands area at 2023. This research used analysis description with cross sectional study. 78 women in fertile age as respondent of this research. Instrument of this research used questionnaire. Data processing used SPSS with chi square test. Result of chi square got relationship knowledge with early detection cancer cerviks equal 0,000 p<0,05). Conclution of this research showed there was relattionsgip between knowledge to ca cervix early detection with IVA method in coastal and islands area at 2023.